2018
DOI: 10.18632/oncotarget.26141
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free miR-494 and miR-21 are disease response biomarkers associated with interim-positron emission tomography response in patients with diffuse large B-cell lymphoma

Abstract: MicroRNA (miRNA)s are dysregulated in Diffuse large B-cell lymphoma (DLBCL), where they reflect the malignant B-cells and the immune infiltrate within the tumor microenvironment. There remains a paucity of data in DLBCL regarding cell-free (c-f) miRNA as disease response biomarkers. Immunosuppressive monocyte/macrophages, which are enriched in DLBCL, are disease response markers in DLBCL, with miRNA key regulators of their immunosuppressive function. Our aim was to determine whether plasma miRNA that reflect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Studies on these immune suppressor cells showed that several miRNAs, such as miR-494, miR-21, miR-30a, miR-155, miR-17-5p, miR-20a, miR-690, and miR-101, could regulate the proliferation, differentiation, and activation of these myeloid cells [59][60][61][62]. In the study by Cui et al, the elevated plasma levels of the MDSCs-associated-miRNAs, miR-494 and miR-21, in DLBCL patients profoundly decreased following 3-6 months of conventional first-line immuno-chemotherapy [58]. Moreover, the kinetic of the reduction of miR-494 expression level was associated with the interim-PET/CT status of the patients.…”
Section: Involvement Of Tme-associated Mirnas In Diagnosis And/or Promentioning
confidence: 98%
See 1 more Smart Citation
“…Studies on these immune suppressor cells showed that several miRNAs, such as miR-494, miR-21, miR-30a, miR-155, miR-17-5p, miR-20a, miR-690, and miR-101, could regulate the proliferation, differentiation, and activation of these myeloid cells [59][60][61][62]. In the study by Cui et al, the elevated plasma levels of the MDSCs-associated-miRNAs, miR-494 and miR-21, in DLBCL patients profoundly decreased following 3-6 months of conventional first-line immuno-chemotherapy [58]. Moreover, the kinetic of the reduction of miR-494 expression level was associated with the interim-PET/CT status of the patients.…”
Section: Involvement Of Tme-associated Mirnas In Diagnosis And/or Promentioning
confidence: 98%
“…However, miRNAs originating from non-malignant tumor-infiltrating cells could also reflect the disease response [57]. MiRNAs that are implicated in regulating the activity of the immunosuppressive components of TME, such as monocytic myeloid-derived suppressor cells (moMDSCs) and tumor-associated macrophages (TAMs), are considered disease response biomarkers in patients with DLBCL [58]. MDSCs are a diverse group of non-lymphoid immune suppressor cells deriving from the myeloid lineage and they function by orchestrating the TME and suppressing anti-tumor immune responses.…”
Section: Involvement Of Tme-associated Mirnas In Diagnosis And/or Promentioning
confidence: 99%
“…Activity, localization and distribution of miRNA are disease biomarkers (Cheng et al, 2015 ; Cui et al, 2018 ), and the above mentioned methods effectively visualize miRNAs in patients as non-invasive imaging systems.…”
Section: Quantification Of Active Mirna: Mirna Activity Reportersmentioning
confidence: 99%
“…As diagnostic biomarkers in DLBCL, a total of eight different miRNAs (miR-15a, miR-21, miR-29c, miR-34a, miR-145, miR-155, miR-210, and miR-375) were found to be significantly dysregulated in at least two different studies. The studies concerning miR-145, miR-375, miR-15a, miR-21 and miR-155 presented the most concordant results, the first two miRNAs being lower and the following three being higher in DLBCL [53,[55][56][57][58][59][60][61][62][63][64][65]. MiR-145 and miR-375 were lower in two studies and are considered tumor suppressors in different cancer types.…”
Section: Micrornamentioning
confidence: 99%